Teachers’ Politeness Strategies in Building Educative Interaction in Elementary Schools - Irma Desni; Erna Ikawati (Jurnal Hata Poda, 2026)
Polite language plays an important role in the learning process because it helps teachers build positiverelationships with students in elementary schools. As language role models, teachers need to use polite,friendly, and easy-to-understand language so that the learning atmosphere becomes comfortable andenjoyable. This study aims to describe how teachers apply language politeness when interacting withstudents and to explain its influence on the learning process. This research uses a qualitative approachwith a descriptive method. Data were collected through classroom observations, interviews withteachers, and documentation, and then analyzed in stages to draw conclusions. The results show thatteachers use various polite language strategies, such as giving instructions in a gentle manner, choosingpositive words, addressing students warmly, and providing verbal praise and encouragement. Theselanguage practices make students feel respected, more confident, and willing to participate actively inlearning activities. In addition, the use of polite language helps develop students’ polite behavior,mutual respect, and positive character. Therefore, teachers’ language politeness functions not only as ameans of communication but also as an important element in character education and in creatingeffective educational interactions.